Determinan of Audit Quality in State-Owned Enterprises Listed on the IDX in 2019-2022 - Lestari, Puji; Anggi, Vika; Sukesti, Fatmasari; Nurcahyono, (UNIMUS Web Conferences, 2025)
Audit quality is the state where auditors uncover misstatements in financial re-ports of a company under audit. The root of this issue lies in the frequent findings of companies presenting inaccurate financial reports, where management tends to manipulate financial statements to enhance positive perceptions among investors. This practice leads to the dissemination of incorrect information and inaccurate decision-making. This study aims to determine the effect of audit tenure, KAP reputation, audit committee, audit fee and auditor independence on audit quality. This study utilizes a population of state-owned enterprises listed on the Indonesia Stock Exchange during the period 2019-2022. The sample consists of 17 state-owned enterprises selected using purposive sampling. Secondary data is used in this research. The analysis method employed is logistic regression analysis using SPSS version 26 software. The results of this study indicate that audit tenure and audit fee have a positive effect on audit quality. The reputation of the public accounting firm has a negative effect on audit quality, while the audit committee does not have an effect on audit quality.